A Escola Nacional de Informações: a formação dos agentes para a inteligência durante o regime militar - Andrade, Fabiana de Oliveira [UNESP] (2014)
The object of this research includes the training of information in Brazil during the military period, more specifically, since the inauguration of the National School of Informations ( NSI ) in 1972. The academic analysis of the School will seek to analyze a) the National Security Doctrin (USD) , developed by the National War College from its inception in 1958 , became the main doctrinal NSI substrate and b) to what extent it is possible to identify the incorporation of the National Security Doctrine in the education of information agents. For this, we analyzed the regional, national and international contexts of thIS time, as well as a comparison between the concepts established by the USD and the instructions given in the manuals, handouts and summaries of classes NSI was established. Thus, to understand the main aspects of the National Security Doctrine and its presence as a major doctrinal basis of the National Information School, will be possible to establish an analysis that is capable of indicating the manner in which the precepts have been adapted and adopted in the formation of intelligence officers formed at the National School of Informations - ESNI